Continuidad y cambio en las prácticas funerarias del bronce final y primera edad del hierro en Menorca - José Simón Gornés Hachero (E-Spania)
To start off of the exhibition of the data that offers the funeral archaeological registry of Menorca, an interpretation sets out on the social change that affected the prehistoric communities which they inhabited the island between the Final Bronze age and the Iron age (1400-800 BC), moment at which appear the first complex rock-cut tombs and turriforms.